2013
DOI: 10.7205/milmed-d-12-00275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Accelerometer on Body Weight and Fitness in Overweight and Obese Active Duty Soldiers

Abstract: This study evaluated whether using a web-linked accelerometer, plus mandatory physical training, is associated with various weight- and fitness-related outcomes in overweight/obese active duty soldiers. Soldiers who failed the height/weight standards of the Army Physical Fitness Test (APFT) were randomized to use a Polar FA20 accelerometer device (polar accelerometer group [PA], n = 15) or usual care (UC, n = 13) for 6 months. Both groups received 1.5 hours of lifestyle instruction. We collected data at baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 13 publications
0
29
0
Order By: Relevance
“…The percentage of women within study samples ranged from 14% to 91% , and of those reporting sex distribution, 71% ( n = 41) had >50% female distribution, with 21% ( n = 13) having ≥70% female distribution. Only five studies had more men than women , and only one of these had >70% male. Of the studies that reported the age of men and women separately, the mean age of male participants ranged from 22 to 63 years and female participants from 21 to 65 years.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The percentage of women within study samples ranged from 14% to 91% , and of those reporting sex distribution, 71% ( n = 41) had >50% female distribution, with 21% ( n = 13) having ≥70% female distribution. Only five studies had more men than women , and only one of these had >70% male. Of the studies that reported the age of men and women separately, the mean age of male participants ranged from 22 to 63 years and female participants from 21 to 65 years.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (31%) were published before 1999 (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43) with the remaining (69%) published from 2000 onwards . Of the 58 studies, 32 (55%) were conducted in the USA (26,27,29,30,(32)(33)(34)(35)(36)(37)39,41,(43)(44)(45)(49)(50)(51)(52)54,57,60,62,65,72,75,76,(78)(79)(80)83,84); 7 in Australia (47,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…168 In fact, in a study of military members who were overweight, the addition of an accelerometer, combined with computer feedback and mandatory physical training, showed no changes in weight, resting heart rate, blood pressure and only one of 28 subjects passed the APFT and Height/Weight standards after 6 months. 169 Clearly, current methods are ineffective at changing behaviors and producing the desired results. Interactions with fitness, nutrition and medical professionals, along with unit leadership could reinforce the healthy habit formation model, which has been shown to produce significantly greater weight loss.…”
mentioning
confidence: 99%